Routine versus early nasogastric decompression in gastrointestinal surgeries: a randomized controlled trial - Patel, Devang H.; Shah, Dharmendra K.; Suthar, Pokhraj P.; Parekh, Pratik M. (International Journal of Research in Medical Sciences, 2017)
Background: Traditionally nasogastric decompression is carried out in post operatively in patients undergoing gastrointestinal surgery. The purpose of the study is to assess the benefits of nasogastric decompression in the early postoperative period as compared to routine nasogastric decompression in patients undergoing gastrointestinal surgeries. Objectives: To assess the benefits of nasogastric decompression in the early postoperative period as compared to routine nasogastric decompression in patients undergoing gastrointestinal surgeries, to assess the complications associated with nasogastric tube insertion, and to assess the effect of early nasogastric tube removal on the patients’ postoperative morbidity and comfort level. Methods: This was a randomized control trial done in the Shree Sayajirao General Hospital, Vadodara. According to patient flow and previous study details the estimated sample size was 300 patients. Patient allotment was 150 patients in each group. Patients admitted on odd dates will be followed for routine nasogastric decompression, and patients admitted on even dates will be followed for early nasogastric decompression. Inclusion criteria for the study include laparotomies performed by any abdominal incisions on emergency as well as elective bases. Variables to be studied were patient comfort (according to patient’s opinion), vomiting (episodes, type, amount, content, on which post-operative day), abdominal distension, appearance of normal bowel sounds, passage of flatus and/or stools (according to patient’s history), incidence of aspiration pneumonia and total duration of the hospital stay with wound complications. Data will be processed and analyzed by chi square test and t-test. Results: In the study total 300 patients were included. No significant difference between both the groups in case of postoperative vomiting with p- value of 0.6028 (i.e. p > 0.05) and abdominal distension with p- value of 0.5183 (i.e. p > 0.05). Significant difference seen in the appearance of the bowel sound in post-operative period with p- value of 0.0002 (i.e. p < 0.05) and passage of flatus or stool with p-value of <0.0001. In case of early decompression group mean postoperative day for the suture removal was 11.9 days and for routine decompression group it was 12.3 days, the difference was statistically significant with p- value of 0.0006 (i.e. p < 0.05). The mean for the total hospital stay for early decompressed group was 10.04 days and for routine decompression group it was 10.47 days which was highly statically significant with p- value of 0.0001 (i.e. p < 0.05). Post-operative wound complication which was statically significance with p-value of 0.0394 (i.e. p < 0.05) and respiratory complications was also significant with p-value of 0.0367 (i.e. p < 0.05). In case of early decompression post-operative nausea, vomiting and abdominal distention were higher but not significant statistically. Conclusions: Early removal of Ryle’s tube leads to less incidence of respiratory complications and wound complications ultimately early suture removal and less hospital stay. Early removal of Ryle’s tube leads to early resolution of postoperative paralytic ileus indicated by early appearance of bowel sounds and early passage of flatus and stool.